Laparoscopic cholecystectomy in left-sided gallbladder detected during operation - Çalışkan, Yahya Kemal; Başak, Fatih; Şişik, Abdullah (Journal of Surgery and Medicine, 2019)
The case where the gallbladder was located on the lower face of the left lateral segment of the liver was defined as a left-sided gallbladder. It is a rare hereditary anomaly and can be seen with the right-sided ligamentum teres. Vascular and biliary anomalies can be seen in the cases of placement anomaly. Full dissection of the calot’s triangle applied as a standard in laparoscopic cholecystectomy is important for the safety of the cases in anomaly cases. In this study, we aimed to present a laparoscopic cholecystectomy performed in a case of a left-sided gallbladder detected during surgery.